Point-of-care testing (POCT) for HIV/STI targeting MSM in regional Australia at community 'beat' locations - Amy B. Mullens; Josh Duyker; Charlotte Brownlow; Jime Lemoire; Kirstie Daken; Jeff Gow (BMC, 2019)
Abstract Background Innovative health promotion strategies are needed to improve access to HIV testing among regional people in Australia, particularly for men who have sex with men (MSM). This project aimed to establish proof of concept for point-of-care-testing (POCT) via a mobile van clinic at community 'beat' locations. Surveys evaluated client satisfaction, characteristics and testing preferences among 'early adopters'. Sequential mixed-methods approach was used which included secondary qualitative analysis of field notes written by peer-testers (i.e., trained lay providers from the key population being targeted; to extend the contextualise the pilot evaluation), documenting barriers/facilitators and innovations, per action research and to guide recommendations for future health promotion initiatives. Methods A POCT 'proof of concept' project (2, 3-hourly sessions/week; 20 weeks) was delivered in a regional town by peer-testers using a mobile clinic van, recruited by geosocial 'apps' targeting MSM. Clients completed surveys regarding demographics, and testing satisfaction, frequency and preferences. Peer-testers completed detailed field notes for each session including client characteristics and impressions, salient events, concerns and recommendations. Results The program resulted in 34 online health promotion conversations with MSM and 34 POCT tests (19 HIV, 15 Syphilis; 18 unique client visits; 17 identified as MSM, with 1 heterosexual female. Rates of satisfaction among early adopters of POCT was high. Analysis of field notes revealed three major themes: 1) Practical challenges; 2) Barriers to engagement; and 3) Recruitment method/project promotion. Conclusions Amongst early adopters satisfaction was high, with 47% of clients reported infrequent testing (over 12 months ago) or having 'never tested'. No tests were reactive. Challenges associated with this health promotion initiative and recommendations for future HIV testing promotion and programs were outlined.